(untitled) (Academicia Globe: Inderscience Research, 2024)
English for Special Purposes (ESP) is an often defined approach to teaching English, focused on the requirements and goals of the learner. ESP is a popular option for teaching English in secondary and tertiary educational institutions in Uzbekistan, especially among students studying automotive engineering language students, especially for academic and professional purposes. There is also a strong emphasis on reading skills that allow students to understand real-world materials related to their majors with ease. This article presents the reader with a theoretical study of the fundamental ideas behind English language proficiency (ESP), including its definition and function as a learning approach. It also discusses related topics such as needs analysis, which is a core feature of ESP, curriculum, learning objectives, materials, methodology, and ESP-based English language teaching assessment.